Cardio-oncology: conflicting priorities of anticancer treatment and cardiovascular outcome - Tilemann, Lisa; Heckmann, Markus B.; Katus, Hugo; Lehmann, Lorenz; Müller, Oliver J. (Clinical research in cardiology, 2018)
BackgroundThis article about the emerging field of cardio-oncology highlights typical side effects of oncological therapies in the cardiovascular system, cardiovascular complications of malignancies itself, and potential preventive or therapeutic modalities.MethodsWe performed a selective literature search in PubMed until September 2016.ResultsCardiovascular events in cancer patients can be frequently attributed to oncological therapies or to the underlying malignancy itself. Furthermore, many patients with cancer have pre-existing cardiovascular diseases that can be aggravated by the malignancy or its therapy. Cardiovascular abnormalities in oncological patients comprise a broad spectrum from alterations in electrophysiological, laboratory or imaging tests to the occurrence of thromboembolic, ischemic or rhythmological events and the impairment of left ventricular function or manifest heart failure.DiscussionA close interdisciplinary collaboration between oncologists and cardiologists/angiologists as well as an increased awareness of potential cardiovascular complications could improve clinical care of cancer patients and provides a basis for an improved understanding of underlying mechanisms of cardiovascular morbidity.
Gesehen am 08.08.2019